THE DEFINITION SECOND ZONE OF SANITARY PROTECTION OF KARBI AND GHAZARAVAN FRESH WATER INTAKES (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
The work is dedicated on the second zone of sanitary protection problem, by using the example of fresh water springs which are exploided for water supply of Ashtarak and Ejmiatsin towns (Karbi and Ghazaravan springs). We calculated the second border of the zones of sanitary protection, which is the main problem for the pollution of springs. It will give an opportunity to keep fresh water springs away from the pollution by restriction of human activity.
Keywords: water intake; groundwater; bacteriological pollution; water bearing horizon